Learning bio-micro-nanotechnology - Mendelson, Mel I (CRC Press, 2013)
Learning Bio-Micro-Nanotechnology is a primer on micro/nanotechnology that teaches the vocabulary, fundamental concepts, and applications of micro/nanotechnology in biology, chemistry, physics, engineering, electronics, computers, biomedicine, microscopy, ethics, and risks to humankind. It provides an introduction into the small world with a low fog index, emphasizing the concepts using analogies and illustrations to simplify the non-observables.